Gel Casting of Free‐Shapeable Ceramic Membranes with Adjustable Pore Size for Ultra‐ and Microfiltration. Issue 5 (2nd April 2014) - Brandes, Christoph; Treccani, Laura; Kroll, Stephen; Rezwan, Kurosch; Gauckler, L.
<x xml:space="preserve">Abstract</x> The growing demand of reliable high‐performance membrane materials for separation processes requires new simple, straightforward, environmental friendly, sustainable approaches for membrane fabrication. In this study, we present an environmentally friendly gel‐casting, one‐pot process based on ionotropic‐gelation for obtaining alumina membranes. A slurry of alumina particles and the biopolymer alginate, which acts in combination with calcium iodate like a resin, was gelled in a controllable temperature dependent manner. Alumina membranes are obtained by three different shaping routes (extrusion, free‐forming, casting). The suitability of extruded capillaries in a polymer‐ceramic hybrid state (green body) and after sintering (1150°C for 2 h) for potential application in micro‐ and ultrafiltration is evaluated by monitoring the chemical and mechanical stability, permeability and separation behavior. Varying the initial alumina particle size from 200 to 900 nm, membranes with a narrow pore size distribution, predictable and tunable average pore diameters from 70 up to 480 nm and a constant open porosity of ~40%, are obtained. The permeability behavior is tested with fluorescence labeled submicron‐ and nano‐particles. Our novel colloidal processing route represents a very versatile tool for designing and manufacturing ceramic membranes with complex shapes for micro‐ (>0.1 μm) and ultrafiltration (0.1–0.01 μm).